Using Discovery Learning Model to Improve Student’s Learning Outcomes in English Learning at SMP Syaichona Cholil Samarinda - Sitti Musarrofah; Abdul Rohman; Godefridus Bali Geroda (Inquest Journal, 2023)
Background: Most students were less active and motivated in participating in English learning. The researcher used this learning model because discovery learning is learning where students learn to discover and try to solve concepts independently Khabibah (2017:146-153)Methodology: The methode of the study was classroom action research (CAR). There were two cycles; each cycle consisted of four steps, they were planning, action, observation, and reflection.Findings: The subjects in this study 25 students. The result of the study shows that the using of discovery learning model to improve students’ learning outcomes in English learning at Syaichona Cholil Junior Hight School Samarinda in the academic year of 2022/2023 was successful. Conclusion: The result of this study, implementation of the discovery learning method in the cycle I was achieved by 91.6%. Then cycle II achieve 100%. The students' cognitive competencies in cycle I was 62.8. Then cycle II, the average student score was 80.4. The percentage of completion in cycle I reach 76%, while achieved 100%. Then the percentage of student activity in cycle I reaches 44%. Then cycle II, increased to 77.2%. Originality: In this study shows that the use of discovery learning model in english learning is successful.